Nicotinic Receptors in Sleep-Related Hypermotor Epilepsy: Pathophysiology and Pharmacology - Andrea Becchetti; Laura Clara Grandi; Giulia Colombo; Simone Meneghini; Alida Amadeo (Brain Sciences, 2020)
Sleep-related hypermotor epilepsy (SHE) is characterized by hyperkinetic focal seizures, mainly arising in the neocortex during non-rapid eye movements (NREM) sleep. The familial form is autosomal dominant SHE (ADSHE), which can be caused by mutations in genes encoding subunits of the neuronal nicotinic acetylcholine receptor (nAChR), Na+-gated K+ channels, as well as non-channel signaling proteins, such as components of the gap activity toward rags 1 (GATOR1) macromolecular complex. The causative genes may have different roles in developing and mature brains. Under this respect, nicotinic receptors are paradigmatic, as different pathophysiological roles are exerted by distinct nAChR subunits in adult and developing brains. The widest evidence concerns α4 and β2 subunits. These participate in heteromeric nAChRs that are major modulators of excitability in mature neocortical circuits as well as regulate postnatal synaptogenesis. However, growing evidence implicates mutant α2 subunits in ADSHE, which poses interpretive difficulties as very little is known about the function of α2-containing (α2*) nAChRs in the human brain. Planning rational therapy must consider that pharmacological treatment could have different effects on synaptic maturation and adult excitability. We discuss recent attempts towards precision medicine in the mature brain and possible approaches to target developmental stages. These issues have general relevance in epilepsy treatment, as the pathogenesis of genetic epilepsies is increasingly recognized to involve developmental alterations.